Hierarchical Action Control: Adaptive Collaboration Between Actions and Habits - Balleine, Bernard W.; Dezfouli, Amir (Frontiers in Psychology, 2019)
It is now commonly accepted that instrumental actions can reflect goal-directed control; i.e., they can show sensitivity to changes in their relationship to and the value of their consequences. With overtraining, stress, neurodegeneration, psychiatric conditions or after exposure to various drugs of abuse goal-directed control declines and instrumental actions are performed independently of their consequences. Although this latter insensitivity has been argued to reflect the development of habitual control, the lack of positive definitions of habits has rendered this conclusion controversial. Here we consider various alternative definitions of habit, including recent suggestions they reflect chunked action sequences, to derive criteria with which to categorize responses as habitual. We consider various theories as to the interaction between goal-directed and habitual controllers and propose a collaborative model based on their hierarchical integration. We argue that this model is consistent with the available data, can be instantiated both at an associative level, using the associative-cybernetic model, and computationally, using hierarchical reinforcement learning, and generates interesting predictions regarding the influence of this collaborative integration on behavior.